ANALISIS METODE PERMAINAN DALAM PEMBELAJARAN BAHASA ARAB KELAS 7 SMP 9 MUHAMMADIYAH BOARDING SCHOOL TANGGULANGIN - Rahmadhani, Gurit; Ammar, Farikh Marzuki (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
This study aims to examine the application of the game method in Arabic language learning for grade 7 of SMP 9 Muhammadiyah Boarding School Tanggulangin. The approach used in this study is qualitative, with the research subjects being grade 7 Putra of SMP 9 Muhammadiyah Boarding School Tanggulangin. Then for the data analysis technique used in this study is